Violence Against Children and Its Relevance to Giving Punishment in Educating Children - Wardana Wardana; Abdul Aziz bin Mustamin (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2020)
Giving punishment as an educational tool used by teachers needs to pay attention to the requirements of a good sentence so that the pedagogical quality can be accounted for. The purpose of punishment in this context is to make children realize their mistakes and not repeat their wrong actions.Islam does not see the application of punishment except as wrong one means if the situation forces them to organize the child and return it to the path of true Islam. Islam does not use punishment except after the use of other means and after society is minimal from crime. The methods adopted by Islam in punishing children are: (a) treating children gently, (b) paying attention to the deviant character of children when applying punishment, (c) looking for solutions gradually, departing from a light way and switching to different ways. weight. This is how Islam requires these punishments and encourages educators to use them. We only need to choose what feels right and can benefit children.